Resident Rotations in Low- and Middle-Income Countries: Motivations, Impact, and Host Perspectives. Issue 3 (July 2020) - Donnelley, Claire A.; Won, Nae; Roberts, Heather J.; von Kaeppler, Ericka P.; Albright, Patrick D.; Woolley, Pierre Marie; Haonga, Billy; Shearer, David W.; Sabharwal, Sanjeev
Abstract : Introduction: Interest in clinical rotations in low- and middle-income countries (LMICs) has grown among high-income country (HIC) orthopaedic residents. This study addresses the following questions: (1) What motivates HIC surgical residents to rotate in LMICs? (2) What is the impact of rotations on HIC residents? (3) What are the LMIC partner perceptions of HIC collaboration? Materials and Methods: A search strategy of multiple databases returned 3, 740 unique articles pertaining to HIC surgical resident motivations for participating in rotations in LMICs or the LMIC host perspective. Data extraction was dually performed using meta-ethnography, the qualitative equivalent of meta-analysis. Results: Twenty-one studies were included in the final analysis. HIC residents were primarily motivated to rotate in LMICs by altruistic intent, with greatest impact on professional development. LMIC partners mostly valued HIC sustained investment and educational opportunities for LMIC partners. From LMIC's perspective, potential harm from collaboration arose from system-level and individual-level discordance between HIC and LMIC expectations and priorities. HIC priorities included the following: (1) adequate operative time, (2) exposure to varied pathology, and (3) mentorship. LMIC priorities included the following: (1) avoiding competition with HIC residents for surgical cases, (2) that HIC groups not undermine LMIC internal authority, (3) that HIC initiatives address local LMIC needs, and (4) that LMIC partners be included as authors on HIC research initiatives. Both HIC and LMIC partners raised ethical concerns regarding collaboration and perceived HIC residents to be underprepared for their LMIC rotation. Discussion: This study synthesizes the available literature on HIC surgical resident motivations for and impact of rotating in LMICs and the LMIC host perception of collaboration. Three improvement categories emerged: that residents (1) receive site-specific preparation before departure, (2) remain in country long enough to develop site-specific skills, and (3) cultivate flexibility and cultural humility . Specific suggestions based on synthesized data are offered for each concept and can serve as a foundation for mutually beneficial international electives in LMICs for HIC orthopaedic trainees.